Assessing Trends in Regional Transfers, Vertical Fiscal Imbalance, and Income Development - Prasetia, Tomy; Baehaqi, Muhammad Nuh (Journal of Business and Economics Research (JBE), 2024)
The complex fiscal links and reliance on central transfers highlight the economic dynamics of regional success in Indonesia, especially in resource-rich areas like Riau. This study primarily adopts the Coefficient of Vertical Imbalance (CVI) framework as an analytical tool to examine the complex patterns of fiscal reliance and vertical fiscal imbalances throughout the districts and cities within Riau Province. Utilizing a descriptive analysis approach, the research meticulously examines secondary data from sources such as the Central Statistics Agency (BPS) and the Online Monitoring of the State Treasury and Budget System (OM SPAN) Regional Office DJPB Riau. Significant changes have been discovered. Districts like Bengkalis and Rokan Hilir, where the ratios of central payments to total regional receipts approach 85%, exhibit a noteworthy level of fiscal reliance. Conversely, urban regions like Pekanbaru and Dumai, with their smaller but still considerable levels of reliance on central transfers, demonstrate the importance of provincial revenue-sharing systems. The analysis also uncovers a complex network of interconnected factors that influence fiscal dynamics, including variations in Total Regional Financial Transfers (TKD) and the efficiency of local government expenditure management. The study's conclusions are vital in forming policy interventions aimed at enhancing fiscal autonomy, optimizing resource distribution, and advancing strategies for sustainable economic growth that are tailored to the specific needs of the several regions in the province of Riau.